2006
DOI: 10.3346/jkms.2006.21.5.854
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Milrinone on the Right Ventriclular Function in Patients with Reduced Right Ventricular Function Undergoing Off-pump Coronary Artery Bypass Graft Surgery

Abstract: This investigation evaluated the effect of continuous milrinone infusion on right ventriclular (RV) function during off-pump coronary artery bypass graft (OPCAB) surgery in patients with reduced RV function. Fifty patients scheduled for OPCAB, with thermodilution RV ejection fraction (RVEF) <35% after anesthesia induction, were randomly allocated to either milrinone (0.5 µg/kg/min) or control (saline) group. Hemodynamic variables and RV volumetric data measured by thermodilution method were collected as follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
(25 reference statements)
0
22
0
Order By: Relevance
“…Of these, the most common reasons for exclusion were as follows: valid data could not be obtained by the authors (87 studies), milrinone was compared with other drugs (17 studies), pediatric populations were used (11 studies), studies were nonrandomized controlled trials (9 studies), crossover studies (5 studies), studies published as abstracts only (4 studies), studies used mechanical devices as controls (4 studies), studies used inhaled milrinone (3 studies), studies used randomization of brain-dead organ donors (3 studies), studies were animal studies (2 studies), and studies used healthy volunteers (1 study). Ultimately, sixteen randomized clinical trials were assessed in compliance with the inclusion criteria (Table 1) [31,[38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, the most common reasons for exclusion were as follows: valid data could not be obtained by the authors (87 studies), milrinone was compared with other drugs (17 studies), pediatric populations were used (11 studies), studies were nonrandomized controlled trials (9 studies), crossover studies (5 studies), studies published as abstracts only (4 studies), studies used mechanical devices as controls (4 studies), studies used inhaled milrinone (3 studies), studies used randomization of brain-dead organ donors (3 studies), studies were animal studies (2 studies), and studies used healthy volunteers (1 study). Ultimately, sixteen randomized clinical trials were assessed in compliance with the inclusion criteria (Table 1) [31,[38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%
“…The total number of patients in the 16 included trials was 698, who underwent CABG surgery (346 treated with placebo/standard care and 352 treated with milrinone) ( Table 2 and Table 3). In ve of these studies, off-pump CABG surgery was performed [31,41,45,46,49], and on-pump CABG surgery was performed in 11 studies [39-45, 48, 49, 51, 52]. As the result showed, the mortality of on-pump CABG between milrinone treatment and placebo/standard care groups, the occurrence was [5/139 (3.59 %) vs. 4/146 (2.74 %), odds ratio (OR) = 1.17 (0.37-3.72), p value = 0.649, I-squared = 0.0%].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Ultimately, sixteen randomized clinical trials were assessed in compliance with inclusion ( Table 1). 32,[39][40][41][42][43][44][45][46][47][48][49][50][51][52]…”
Section: Resultsmentioning
confidence: 99%
“…27,28 Milrinone, one of the PDE III inhibitors, primarily used after openheart surgery because it can avoid cardiopulmonary bypass, 29 enhances cardiac contractility, 30 prevents vasospasm, 31 and ameliorates low output syndrome (LOS). (32) However, recent studies have demonstrated that the efficacy and safety profile of milrinone remain controversial, although it is implemented in several guidelines. 33,34 In some cardiac surgeries, the tendency of increasing mortality and incidence of arrhythmia was found in milrinone group, comparing with control agents.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used alone or in combinations in patients with decompensated heart failure, particularly in those with nonischemic left ventricular systolic dysfunction (Mehra et al 1997; elker et al 2003) and cardiac surgery patients (Levy et al 2002; Lee et al 2006). In animal models of both acute and chronic pulmonary hypertension, milrinone significantly reduced PVR and improved RV function (Chen et al 1997; Hashiba et al 2000).…”
Section: Management Of Arterial Pulmonary Hypertension In Noncardiac Icumentioning
confidence: 99%